A study to assess factors contributing for the occurrence of incisional hernia among patients operated with pfannenstiel incision and management with mesh repair - Nalini, Y. Lakshmi; Puvvala, Manipal Kumar; Chandra, A. Sarath; Rajalingam, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Incisional hernia is due to failure of lines of closure of abdominal wall following laparotomy. Bowel or a part of bowel or omentum can bulge through the gap. The early occurrence (within 5 years) is mainly due to early sepsis and obesity. Objective of present study was to assess the factors contributing for the occurrence of incisional hernia. Methods: All the women who were operated between March 2014-December 2016 using a low transverse Pfannenstiel incision and who did not have any other lower (vertical) incisions and laparoscopic surgeries were followed up in the outpatient department. 1,252 cases were followed up during the above-mentioned period and the detail history was elicited and meticulous physical examination was conducted. USG Abdomen was done in all the cases. Out of 1,252 cases 25 were having incisional hernia and mesh repair was done for incisional hernia. Results: Nearly 2% of these cases had incisional hernia. Obesity was the main risk factor in 36% of the study participants followed by wound infection in 32%. Conclusions: Obesity, redo surgeries, size of the incision and type of suture materials used contribute to the formation of incisional hernia. Although the incidence is low still incisional hernia can occur following Pfannenstiel low transverse abdominal incision.